Proceedings of the 1st ACM/USENIX International Conference on Virtual Execution Environments 2005
DOI: 10.1145/1064979.1064994
|View full text |Cite
|
Sign up to set email alerts
|

Planning for code buffer management in distributed virtual execution environments

Abstract: Virtual execution environments have become increasingly useful in system implementation, with dynamic translation techniques being an important component for performance-critical systems. Many devices have exceptionally tight performance and memory constraints (e.g., smart cards and sensors in distributed systems), which require effective resource management. One approach to manage code memory is to download code partitions on-demand from a server and to cache the partitions in the resource-constrained device … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Although more sophisticated eviction policies are possible, flushing the F$ is a simple one that is used to minimize the overhead of managing the F$ [5,11,27]. The problem with this approach is that fragments which are soon needed can be evicted, especially for a small F$.…”
Section: Victim Compressionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although more sophisticated eviction policies are possible, flushing the F$ is a simple one that is used to minimize the overhead of managing the F$ [5,11,27]. The problem with this approach is that fragments which are soon needed can be evicted, especially for a small F$.…”
Section: Victim Compressionmentioning
confidence: 99%
“…The management of the F$ has been widely studied for general-purpose systems and large fragment caches [2,3,4,5,11,21,23,27]. Bala et al suggested the strategy of flushing the F$ when it becomes full [2].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Strata has been used for a variety of applications including system call monitoring, dynamic download of code from a server, and enforcing security policies [12,25]. This section describes some of the basic features of Strata which are important to understanding the experiments presented later.…”
Section: Stratamentioning
confidence: 99%